2022
DOI: 10.1108/ribs-05-2021-0068
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing supply chain agility to enhance export performance: case of export-oriented textile sector

Abstract: Purpose This study aims to examine the effect of supply chain agility (SCA) on the export performance of the Pakistani textile industry. Despite being one of the leading manufacturing and exporting sectors, only a handful of the extant literature is found on the textile industry. Design/methodology/approach A structured questionnaire was prepared using the extant literature. Data was gathered from 146 respondents associated with the textile industry of Pakistan. Hypotheses were tested using structural equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…In this respect, Gligor et al (2022) demonstrate that papers with different SCA definitions use the same measurement scale and papers with similar SCA conceptualisations propose different scales, which supports the SCA scale's use as a moderator rather than the SCA conceptualisation. In this sense, in most cases (see Table A-Online Appendix), SCA has been operationalised as a first-order construct based on a variety of scales constructed with a very different number of items ranging from a minimum of 3 items (Khan et al, 2023;Garcia-Alcaraz et al, 2017) to a maximum of 28 (Geyi et al, 2020). A broad range is also found when SCA is a second-order construct, with between two (Zakir et al, 2022) and six (Sangari and Razmi, 2015) dimensions defined.…”
Section: Moderators In the Sca-performance Relationshipmentioning
confidence: 99%
“…In this respect, Gligor et al (2022) demonstrate that papers with different SCA definitions use the same measurement scale and papers with similar SCA conceptualisations propose different scales, which supports the SCA scale's use as a moderator rather than the SCA conceptualisation. In this sense, in most cases (see Table A-Online Appendix), SCA has been operationalised as a first-order construct based on a variety of scales constructed with a very different number of items ranging from a minimum of 3 items (Khan et al, 2023;Garcia-Alcaraz et al, 2017) to a maximum of 28 (Geyi et al, 2020). A broad range is also found when SCA is a second-order construct, with between two (Zakir et al, 2022) and six (Sangari and Razmi, 2015) dimensions defined.…”
Section: Moderators In the Sca-performance Relationshipmentioning
confidence: 99%
“…This is due to the constant change in the environment in terms of technology, untimely market pressures and globalization (Jermsittipersert and Wajeetongratana, 2019). Hence, to stay competitive globally in the present circumstances, supply chain agility has become an essential component of a firm's performance (Khan et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Supply chain agility has gained popularity because of the increased changes in the market since it is the only path to quickly respond to these changes to fulfill customer demands (Ganguly et al ., 2017; Jermsittipersert and Wajeetongratana, 2019). Supply chain agility refers to the ability of a firm to respond quickly and flourish in competitive markets, which are characterized by unpredictable and constant change (Khan et al ., 2022). Previous literature showed that supply chain agility is generally expected to improve performance (Chan et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations